1998
DOI: 10.1007/s004670050421
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical activation of lupus nephritis by recombinant human growth hormone

Abstract: The effect of growth hormone (GH) on subclinical disease activity in a 15-year-old boy with previously quiescent lupus nephritis and chronic renal failure is described. Institution of supraphysiological doses of GH resulted in a rise in erythrocyte sedimentation rate, decrease in serum complement, rise in anti-DNA antibody titers, and increase in T-cell activation markers, all of which improved following cessation of GH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In this way, chronic high GH/IGF-I levels in Tg mice would produce an autoimmune-like pathology that closely resembles that described in MRL mice (Cohen & Eisenberg 1991). Furthermore, recent reports showing the anti-apoptotic effect of GH and IGF-I support this notion (Kulik & Weber 1998, Haeffner et al 1999 and would also explain the subclinical activation of lupus nephritis reported by GH administration (Yap et al 1998). However, further works need to be performed in order to understand the mechanism underlying the autoimmune-like process displayed in Tg mice.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this way, chronic high GH/IGF-I levels in Tg mice would produce an autoimmune-like pathology that closely resembles that described in MRL mice (Cohen & Eisenberg 1991). Furthermore, recent reports showing the anti-apoptotic effect of GH and IGF-I support this notion (Kulik & Weber 1998, Haeffner et al 1999 and would also explain the subclinical activation of lupus nephritis reported by GH administration (Yap et al 1998). However, further works need to be performed in order to understand the mechanism underlying the autoimmune-like process displayed in Tg mice.…”
Section: Discussionmentioning
confidence: 68%
“…Our results suggest that bGH Tg mice are a suitable animal model to address the pathogenesis of arthritic processes and the mechanism by which sustained high GH/IGF-I levels cause immunological disorders. In addition, the side-effects described in humans following exogenous GH administration such as oedema and a subclinical activation of lupus nephritis (Yap et al 1998) are related to the bGH Tg murine model.…”
Section: Introductionmentioning
confidence: 99%
“…They also concluded that the role of the neuroendocrine-immune system in adult SLE was, at the present time, limited to deficiencies in prolactin. Of note, two recent case reports suggested a link between growth hormone and exacerbation of lupus nephritis in a male teenager with SLE [28] as well as in juvenile SLE [29] where when growth retardation treated with growth hormone was terminated, clinical improvement in lupus symptoms was observed. These findings suggested that exogenously-administered growth hormone may result in "toxic" levels of growth hormone accompanied by lupus "flares" with progressive autoimmune dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…GH therapy may change the disease activity in GC-treated autoimmune diseases in which T lymphocytes play a major role in controlling immune functions. Indeed, one study has indicated that GH therapy raised the activity of autoimmune diseases, including systemic lupus erythematosus treated with GC (8).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is unclear whether GH can be used safely in autoimmune disorders that are treated with GC. Indeed, a previous study has shown that GH therapy increased the disease activity in systemic lupus erythematosus patients (8). In this study, we focused on the effect of GH on peripheral T lymphocytes under GC excess.…”
mentioning
confidence: 99%